TI_GERICHTE 52.2015.175 vom 6. April 2016 , Licenza edilizia per uno stabile su un fondo in riva al lago Ceresio - TI Tribunale d'appello (2016)
Licenza edilizia per uno stabile su un fondo in riva al lago Ceresio